Study to evaluate the acaricidal efficacy of a single topical treatment with a topical combination of fipronil/amitraz/(S)-methoprene against Dermacentor variabilis on dogs - Dryden, Michael W.; Smith, Victorene E.; Kunkle, Bruce; Carithers, Doug (My University, 2012)
The objective of the study was to confirm the acaricidal efficacy of a single topical treatment of the combination of fipronil/amitraz/(S)-methoprene (CERTIFECT®) against induced infestations of Dermacentor variabilis. Sixteen healthy mixed breed mongrels (8 males and 8 females), approximately 9.6 to 13.7 months of age on Day 0, and weighing 16.2 to 33.4 lbs, were selected from a group of 20 dogs based on Day -1 pre-treatment tick counts to be utilized in this randomized, blinded efficacy study. Eight dogs were randomly assigned to one of the two treatment groups: Group 1 - placebo (vehicle), Group 2 - fipronil/amitraz/(S)-methoprene (delivering at least 6.7mg fibronil/kg body weight (bw), 8.0 mg amitraz/kg bw, and 6.0 mg (S)-methoprene/kg bw). The vehicle or treatment was applied directly onto the skin at two separate spots on the neck of each dog, once on Day 0, per label dose and directions for use. All dogs were infested with 50 (±5) unfed adult D. variabilis on Day 1, then weekly on days 7, 14, 21, 28, and 35. Ticks were thumb counted at 24 (±3) hours following each tick infestation and subsequently were counted and removed from each dog at 48 (±3)hours after tick infestation. Thumb counts were performed on all dogs at 24 hours following each infestation. Efficacies on Days 2, 8, 15, 22, 29, and 36 were 98.6, 100, 99.7, 96.6, 86.6, and 90.1%, respectively. All dogs treated with the fipronil/amitraz/(S)-methoprene product had significantly (p<0.05) fewer ticks than placebo (vehicle-treated) control animals. Removal counts were performed at 48 hours after each infestation. Efficacies for Days 3, 9, 16, 23, 30, and 37 were 100, 100, 100, 100, 99.4, and 97.2%, respectively. Again, all dogs treated with the fipronil/amitraz/(S)-methoprene product had significantly (p<0.05) fewer ticks than placebo (vehicle-treated) control animals. No treatment related adverse events were observed during the study, including during four observations performed within 5 hours post-treatment. The results of this study confirm rapid and effective control of D. variabilis ticks on CERTIFECT-treated dogs.
Keywords: Dermacentor variabilis; Fipronil/amitraz/(S)-methoprene; Ticks; Speed of kill; Acaricide